Makroalger som resurs En sammanställning av näringsåtervinning, vattenrening och möjligheter inom livsmedelsindustrin - Albinson, Joel; Anglefalk, Victoria; Isberg Stjerna, Minna; Johnson, Hampus; Neuenschwander, Stina; Nordholm, Per (My University, 2025)
The aim of this paper is to provide an overview of macroalgae (sugar kelp and sea lettuce) growing along the Swedish west coast and to explore its potential applications as a protein source and a biofilter for wastewater treatment as well as an integrated part of a fish farm. The methods used include a comprehensive meta-analysis, study visits and interviews with experts in the field. Different case studies were conducted, with the primary aim of calculating the nitrogen and phosphorus uptake of sea lettuce to assess its potential for filtering wastewater from various sources. Although the aim was to conduct research on both sugar kelp and sea lettuce, the primary focus and case studies were centered around sea lettuce due to the limited existing research on sugar kelp. The results showed that the protein content of macroalgae could be increased when cultivated in wastewater with high concentrations of nitrogen and phosphorus. However, sugar kelp did not survive under such conditions. The elevated protein content may position macroalgae as a potential competitor to established protein sources such as fish. When combining wastewater treatment with macroalgae cultivation, results showed that the water could be effectively filtered. This approach could involve integrating macroalgae cultivation into the effluent stream of a wastewater treatment plant located in the harbor in Gothenburg. In conclusion, integrating macroalgae cultivation with wastewater treatment plants could enhance water filtration and improve the quality of the effluent released into the sea. This approach may contribute to mitigating the problem of eutrophication. Regarding its potential as a plant-based protein source, macroalgae cultivation shows great promise, particularly when integrated with the fish industry. However, the practical implementation in society and industry presents several challenges. Further research, as well as investments, is needed to enable large-scale adoption.